Relics of the Late Mediaeval Defensive Residence in Zawalów Kolonia in the Light of Geophysical Research - Ordutowski, Jakub (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2010)
Author considers geophysical research focusing on localization and recognition of the defensive structures and residential buildings of a the Late Mediaeval motte and bailey earthwork at Zawalów Kolonia in eastern part of Poland. The motte that is the subject of this paper is one of the largest and best surviving of its kind in Poland. In the survey the magnetic method was used with a Geoscan Research fluxgate gradientometer FM 256 with 0.1 nT resolution.
Relikty późnośredniowiecznej rezydencji obronnej w Zawalowie Kolonii w świetle badań geofizycznych
Keywords: Late Mediaeval period; defensive residence; geophysical research; Zawalów Kolonia